Integrated pest management and the small farmers in Malaysia - Hussein, Mohd Yusof
The era of integrated pest management (IPM) is here to stay in the developing countries throughout the world. Most IPM programmes in developing countries like Malaysia currently underway focus attention on pesticide management and the integration of other pest control measures, particularly the traditional methods. Given the conditions that existed and persisted in Malaysia, the current position of IPM can be considered as favourable. Currently, more attention is being given to educating the public, particularly the small farmers, training of pest managers and research on selective use of pesticides. Research conducted in plots and small fields on selective use of pesticides has produced encouraging results. For example, research conducted by the Malaysian Agricultural Research and Development Institute (MARDI) showed that growing of cabbages in the highlands using IPM strategies gave similar returns, if not better. The University of Agriculture has also conducted research on integrated control